Dynamics of the heart rate variability and oxygen saturation response to acute normobaric hypoxia within the first 10 min of exposure - Krejčí, Jakub; Botek, Michal; McKune, Andrew J (Clinical physiology and functional imaging, 2018)
Although the heart rate variability (HRV) response to hypoxia has been studied, little is known about the dynamics of HRV after hypoxia exposure. The purpose of this study was to assess the HRV and oxygen saturation (SpO2 ) responses to normobaric hypoxia (FiO2 = 9·6%) comparing 1 min segments to baseline (normoxia). Electrocardiogram and SpO2 were recorded during a 10-min hypoxia exposure in 29 healthy male subjects aged 26·0 ± 4·9 years. Baseline HRV values were obtained from a 5-min recording period prior to hypoxia. The hypoxia period was split into 10 non-overlapping 1-min segments and time domain HRV indexes (RMSSD and SDNN) were calculated for each segment. Differences (Δ) from baseline values were calculated and transformed using natural logarithm (Ln). This study revealed that the decrease in ΔSpO2 became significant (P<0·001) in the first minute of hypoxia, the decrease in ΔLn RMSSD became significant (P = 0·002) in the second minute, and the decrease in ΔLn SDNN became significant (P = 0·001) in the third minute. Between the second and fifth minute of hypoxia, ΔSpO2 correlated with ΔLn RMSSD (r = 0·57, P<0·001) and ΔLn SDNN (r = 0·44, P<0·001). Five min after the onset of hypoxia, ΔSpO2 was significantly (P = 0·002) decreased but changes in ΔLn RMSSD (P = 0·344) and ΔLn SDNN (P = 0·558) were not significant. In conclusion, the decrease in HRV was proportional to desaturation but only during the first 5 min of hypoxia.
Keywords: autonomní nervový systém; elektrokardiografie; hypoxie; Hypoxia; Altitude Sickness; Time Factors; aklimatizace; time domain; mužské pohlaví; autonomic nervous system; Adult; mladý dospělý; Acclimatization; Heart Rate; srdeční frekvence; exponential decay; kyslík; Young Adult; Electrocardiography; výšková nemoc; Humans; simulated altitude; Autonomic Nervous System; Altitude; biologické markery; časové faktory; root mean square successive difference; Heart; nadmořská výška; Oxygen; dospělí; Biomarkers; srdce; lidé; Male